Relationship among adiponectin, insulin resistance and atherosclerosis in non-diabetic hypertensive patients and healthy adults - Huijuan Kou; Jie Deng; Dengfeng Gao; Anqi Song; Zhenhua Han; Jin Wei; Xin Jin; Rui Ma; Qiangsun Zheng (Clinical and Experimental Hypertension, 2018)
Adiponectin, which is secreted specifically by adipose tissue, has been shown to have anti-atherogenic and anti-inflammatory effects and to improve insulin resistance (IR). The aim of this study was to determine the correlations among adiponectin, IR and atherosclerosis in non-diabetic hypertensive patients and healthy volunteers. In this case control study, we collected complete demographic data from and measured several laboratory parameters in all enrolled subjects. The homeostasis model of assessment for insulin resistance (HOMA-IR) was calculated as an insulin sensitivity index. The atherogenic index of plasma (AIP), which is calculated as log (triglyceride (TG)/high-density lipoprotein cholesterol (HDL-C)), was a significant predictor of atherosclerosis and was a better predictor of atherosclerosis than low-density lipoprotein cholesterol (LDL-C). Plasma adiponectin, interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1) and matrix metalloprotein-9 (MMP-9) concentrations were determined using enzyme-linked immunosorbent assay (ELISA). All data were analyzed using Statistical Product and Service Solutions for Windows (SPSS) 13.0 software. A total of 309 participants were enrolled in the study. Hypertensive patients with IR (n = 93) displayed significantly higher HOMA-IR values and AIPs and lower adiponectin levels than hypertensive patients without IR (n = 121) and healthy adults (n = 95) (P < 0.05). Furthermore, circulating IL-6, MCP-1 and MMP-9 concentrations differed significantly between hypertensive patients and healthy adults (P < 0.05). Additionally, adiponectin levels were found to be inversely correlated with IL-6, MCP-1, and MMP-9 levels; HOMA-IR values; and AIPs in the clinical study. HOMA-IR values and adiponectin and creatinine (Cr) concentrations remained independently associated with AIPs in all participants after adjustment for confounders via multivariate linear regression. Low adiponectin levels are positively correlated with decreased insulin sensitivity, increased pro-inflammatory cytokine production and worsening atherosclerosis in hypertensive patients and healthy adults.